Sustainable Food Production and Nutraceutical Applications from Qatar Desert Chlorella sp. (Chlorophyceae) - Rihab Rasheed (14153385) (2020)
Microalgae isolated from the Qatari desert was identified as thermotolerant, with a rich metabolite profile that is appropriate for use as food and health supplements. In this research, a species of Chlorella, QUCCCM3, from the Qatar University Culture Collection of Cyanobacteria and Microalgae, was investigated for its growth characteristics and metabolite compositions for use as potential feedstock for food production. The strain was cultivated at 30, 35, and 40 °C, covering the annual average low and high temperatures in Qatar. The highest growth rates were recorded for cultures at 30 °C with 0.64 ± 0.04 day−1, followed by a growth rate of 0.54 ± 0.06 day−1 at 40 °C, indicating its thermotolerance ability. The biomass exhibited a high protein content (43 ± 2.3%), with existence of lysine (4.13%) as an essential amino acid, and docosahexaenoic acid, linoleic acid, and alpha-linolenic acid as important omega fatty acids present. On the other hand, Chlorella sp. QUCCCM3 also exhibited a high capacity for scavenging free radicals with an antiproliferative effect against chronic myeloid leukemia K562 cancer cells. The results indicate that Chlorella sp. QUCCCM3 is a promising candidate that can be produced year-round, in the Qatar environment, for commercial applications such as feed and nutraceutical supplements. Other Information Published in: Animals License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ani10081413